Elaboração de um guia de consulta rápida de interações medicamentosas de caráter contraindicado - Ferreira, Fabiana Sari (2023)
The drug interaction can be understood as a pharmacological or clinical response of results from the combination of two or more drugs composed. One drug maybe altered in function of another, which may have consequences in the therapy of several diseases. Some drug interactions can cause potential harm, exposing the patient to risks that are often unnecessary and increasing the length of hospital stay. For this reason, the objective of this work was to develop a means of quick search for drug interaction to favor and optimize the pharmacist’s routine. The search for drug interactions, carried out through the support tool Micromedex®. From the collected and spreadsheet drug interaction data, a table was elaborated, where a combination of drugs is made by crossing the information (lines x column), representing a contraindicated drug intereactions when the corresponding table is red. 224 medications were counted, of which 45 medications originate 54 contraindicated-type drug interactions among the standardized medications in the institution. The dispersion of the amount of drug interaction for each medication was found to be discrepant for methylene blue and bromopride (for 8 interactions each) and linezolid (13 interactions). In this way, it was possible to perceive that all drugs, including that least number of contraindicated interactions with standardized drugs in the institution in question, need attention and care during their prescription, dispensation and administration, eliminated as contraindicated associations, however when this does not If possible, monitoring and follow-up of the patient are essential and, therefore, the availability of quick search tools to identify drug interactions is of great importance in the pharmacist’s routine.